Increasing breastfeeding rates among African-American women enrolled in the Special Supplemental Nutrition Program for Women, Infants, and Children: application of Social Cognitive Theory. Issue 1 (2nd January 2017) - McKinley, Erin; Turner, Lori
ABSTRACT: Breastfeeding offers tremendous health benefits to both child and mother. In spite of these many benefits, current rates of breastfeeding initiation, duration, and exclusivity among African-American women enrolled in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) are lower than rates of other ethnic groups. The decision to breastfeed is complicated, and strategies are needed to increase breastfeeding rates among these women. Social Cognitive Theory (SCT) offers hope for understanding these complicated decisions and for developing strategies to overcome this problem. The purpose of this paper is to explore the literature and develop strategies based on SCT to increase breastfeeding among African-American women enrolled in WIC.